Algorithm awareness: Why user awareness is critical for personal privacy in the adoption of algorithmic platforms?. (August 2022) - Shin, Donghee; Kee, Kerk F.; Shin, Emily Y.
Abstract: Understanding how algorithms shape users' online experiences is a prerequisite to developing an effective algorithm design. Due to the rapid algorithmification of platforms, it is timely to examine users' awareness of algorithms on online platforms because these algorithms can shape everyday decisions and interactions through mediating, gatekeeping, and structuring user interactions. Focusing on the role of algorithm awareness (AA) in the privacy calculus process, we investigate users' intention to disclose personal information when using a platform with personalized algorithms. By conceptualizing AA with a range of theoretical and behavioral variables, we examine how users' self-efficacy affects their privacy concerns when they adopt, consume, and interact with such platforms. The findings show that AA leads users to envisage, understand, and interact with algorithms depending on their understanding of the control of the information flow embedded within them. The awareness that users have regarding algorithms influences the trust of algorithmic processes and the way users evaluate privacy concerns and self-disclosures. The cognitive user processes of AA provide conceptual frameworks for algorithm design and a practical guideline for the design of personalized algorithms. Highlights: The roles algorithmic awareness (AA) plays in the adoption of online streaming platforms. How users respond to the algorithms. User intention to disclose information from the Privacy Calculus framework. Significant effects of user awareness on sharing personal data with algorithms. Clarifying the users' sensemaking process concerning the privacy calculus process.